(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
Four Pleistocene bathyal molluscan assemblages from southern Italy (Calabria and Messina area) were studied. One hundred and thirty-six species were recorded. Twenty-four were classified and described in detail and thirty-five were illustrated. The following new combinations are pro posed: Solariella marginulata (Philippi, 1844), Iphitus tenuisculptus (Seguenza, 1876), Benthomangelia tenuicostata (Seguenza, 1879), Chrysallida microscalaria (Seguenza, 1876), Ennucula corbuloides (Seguenza, 1877), Ennucula rotundata (Seguenza, 1877), Thestyleda cuspidata (Philippi, 1844), Katadesmia confusa (Seguenza, 1877), Austrotindaria pusio (Philippi, 1844), Austrotindaria salicensis (Seguenza, 1877). Comments concerning the taxonomy of Fissurisepta Seguenza, 1862, Solariella Wood, 1842, Ennucula Iredale, 1931, Thestyleda Iredale, 1929, Ledella Verrill & Bush, 1897, Yoldiella Verrill & Bush, 1897, Bathyspinula Filatova, 1958, Katadesmia Dall, 1908, Austrotindaria Fleming, 1948 and Cadulus Philippi, 1844 are included. The assemblages are dominated by nuculoids and fit the general compositional pattern of the deep-sea molluscan communities. A paleodepth of 500-600 m is inferred for two assemblages, whereas a greater depth, pro bably not exceeding 1,000 m, is suggested for the other two. Taxonomic affinities with northeast Atlantic and more generally with World Ocean deep-sea molluscan faunas are remarkable. The Plio-Quaternary evolution of the deep Mediterranean benthos is discussed.